2014
DOI: 10.1021/jp510242h
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Adsorption and Dissociation of Water Clusters on Flat and Stepped Metallic Surfaces

Abstract: Understanding the structure and chemical reactivity of water adsorbed at metallic surfaces is very important in many processes such as catalysis, corrosion, and electrochemistry. Using density functional theory calculations, we investigate the adsorption and dissociation of water clusters on flat and stepped surfaces of several transition metals: Rh, Ir, Pd, and Pt. We find that water binds preferentially to the step edges than to terrace sites, thus linear clusters or one-dimensional water wires can be isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 71 publications
11
39
0
Order By: Relevance
“…11 The (211) and (221) stepped surfaces, mimicking the edges of realistic nanoparticles, have been found to be more reactive towards water, which is likely due to the lower coordination of the surface sites. 10,11 These findings are in line with the computational reports by Calle-Vallejo et al…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…11 The (211) and (221) stepped surfaces, mimicking the edges of realistic nanoparticles, have been found to be more reactive towards water, which is likely due to the lower coordination of the surface sites. 10,11 These findings are in line with the computational reports by Calle-Vallejo et al…”
Section: Introductionsupporting
confidence: 91%
“…The adsorption energies on the extended surface models indicate that water favors the E site on the stepped (211) surfaces over the terrace sites on the (111) and (100) surfaces in line with the previous computational reports. [9][10][11][12][13][14][15][16][17][18] The 7 Overall, the highly undercoordinated C sites of the nanoparticles bind water the strongest, as intuitively expected, followed by the E, 100T, and 111T sites in the same order as for the extended surface models.…”
Section: -21supporting
confidence: 55%
See 1 more Smart Citation
“…Theoretical studies indicated that surface defects, e.g. steps, cause significant disruptions of extended water frameworks [13][14][15][16][17].…”
mentioning
confidence: 99%
“…The exact nature of the adsorption structure was not resolved. In recent years, multiple theoretical studies have addressed water adsorption and solvation along platinum step edges [13][14][15]22]. In these studies, water was found to form one-dimensional (1D) lines along the step edge.…”
mentioning
confidence: 99%